Given the equation
![\begin{gathered} 3\text{ }\sqrt[5]{(x+2)^3\text{ }}\text{ + 3 = 27} \\ \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/high-school/5p1qr2q42hj9bczs51aw17ttylrf1f3581.png)
Subtract 3 from both sides
![\begin{gathered} 3\text{ }\sqrt[5]{(x+2)^3\text{ }}\text{ + 3-3 = 27}-3 \\ \\ 3\text{ }\sqrt[5]{(x+2)^3\text{ }}\text{ = }24 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/high-school/2bghmr3haq3vf4dcojych1raparob062ra.png)
Divide both sides by 3
![\begin{gathered} \text{ }\sqrt[5]{(x+2)^3\text{ }}\text{ = }(24)/(3) \\ \text{ }\sqrt[5]{(x+2)^3\text{ }}\text{ = 8} \\ \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/high-school/6zjtrtwvli6d62ag03lqtybvr5sgwkvuj5.png)
Raise both sides to power 5 to remove the 5th root on the left hand side
![\begin{gathered} \text{ (}\sqrt[5]{(x+2)^3\text{ }})^5=8^5 \\ \\ (x+2)^3=(8^{})^5 \\ (x+2)^3=\text{ 32768} \\ \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/high-school/ndd8264sshgnwb6rshay2zisfn5itmsgkr.png)
Take the cube root of both sides
![\begin{gathered} \sqrt[3]{(x+2)^3}^{}=\sqrt[3]{32768} \\ (x+2\text{ )= 32} \\ \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/high-school/i2g2wp116y5ben4yq8lbm33mdxssrfbm5e.png)
Subtract 2 from both sides
x + 2 = 32
x = 32 - 2
x = 30
The solution to the equation is x = 30